The Use of Youtube as an English Learning Media at Management Program Study of Universitas Mahkota Tricom Unggul - Roni Juliansyah; Masniati Murni Ritonga (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The demanding situations of the arena of training in assembly the wishes of the internet era are pretty large. This is because of their extraordinary existence experiences, particularly their enjoy in the usage of technology. The internet itself opens up many possibilities for integrating technology in classroom learning. Youtube is one of the getting to know media that may be incorporated in getting to know publications which can be taken into consideration hard with the aid of using students.. The purpose of this research is to be able to find out the benefits that can be taken from youtube for English learning media in English courses. This research is a qualitative research in which the author uses observation, question and answer (interview) and questionnaire. The results of the study show that videos on Youtube can be used as one of the learning media.